Polanyi, the Failed Prophet of Moral Economics - Adelman, Jeremy (Boston Review, 2017)
Polanyi gave us a vital counterpoint to the hegemony of political economics. But how far can he take us?
Keywords: biography; critique

An Economic Prophet for Our Time - Iber, Patrick (The Chronicle of Higher Education, 2017)
Karl Polanyi knew the market couldn’t solve all ills. History is proving him correct.
Keywords: Karl Polanyi: A Life on the Left (Book); SANDERS, Bernie; TRUMP, Donald

Karl Polanyi, The Great Transformation and a New Political Economy - Watson, Matthew; Holmes, Christopher; Clift, Ben (brunobertez, 2017)
Karl Polanyi, The Great Transformation and a new political economy Professor Matthew Watson, Assistant Professor Christopher Holmes and Professor Ben Clift, Politics and International Studies Avert…
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; KEYNES, John Maynard, 1883-1946; MARX, Karl, 1818-1883

Polanyi against the whirlwind - Guinan, Joe; Hanna, Thomas M. (Renewal (0968252X), 2017)
The author argues that market liberalism should be stopped if the 21st century generation is to avoid the re-emergence of fascism and environmental collapse. The author calls on the political left to offer a different political economy to avoid the consequences of market liberalism and warns against economist Karl Polanyi's assertion that market liberalism always leads to the erosion of society's human and natural substance. He also discusses the reasons for the political turmoil in the U.S.
Keywords: environmental monitoring; fascism; liberalism; market liberalism; right & left (political science)